CORRELATION OF WORKLOAD AND JOB STRESS WITH DOCTOR PERFORMANCE IN THE ER AND INPATIENT UNITS OF TEBO REGIONAL HOSPITAL (International Journal of Cultural and Social Science, 2026)
The Emergency Department (IGD) and inpatient wards are critical units in a hospital that require highly skilled and responsive medical personnel. This study aims to analyze the relationship between workload and job stress with the performance of doctors at RSUD TEBO. A cross-sectional analytical survey was conducted involving a total population of 32 general practitioners. Data were collected through questionnaires covering workload indicators (time, mental, and psychological effort), job stress levels, and clinical performance dimensions. The results were analyzed using Chi-Square tests. The findings indicate a significant relationship between workload and doctor performance (p-value = 0.000) and between job stress and doctor performance (p-value = 0.000). High workloads and excessive stress levels were found to negatively impact clinical performance. This study concludes that managing medical personnel's workload and providing stress mitigation strategies are essential to maintain high-quality healthcare services.